What is the Role of Carbon Taxes in Climate Change Mitigation? - Aldy, Joseph (World Bank, Washington, DC, 2012)
This note argues that a carbon tax system is more practical to implement, monitor and enforce than tradable permit-based approaches to global climate-change action. It suggests that a sensible design will be an upstream carbon tax on the fossil fuel supply chain, which can also include other major non-(carbon monoxide) CO2 greenhouse gases (GHGs). While risks such as fiscal cushioning exist, a tax-based system will be more transparent and offer the appropriate incentives for participation and compliance.